Research on Multi-Machine Pre-Synchronization Control and Optimization Based on Parallel Recovery Black Start - Zhongping Ruan; Shuye Ding; Yizhi Chen (Energies)
With the increasing prevalence of renewable energy, microgrids play a crucial role in enhancing distributed energy efficiency and system flexibility. However, the intermittent and unpredictable nature of renewable energy generation presents significant challenges for microgrid restoration and stable operation. Black-start technology, a key method for autonomous power restoration, is essential for ensuring reliable microgrid operation. Grid-forming virtual synchronous generators (VSGs), with inherent inertia support and regulation capabilities, autonomously establish the voltage, meeting the power supply demands of black-start processes. However, during the pre-synchronization of multiple distributed energy resources in black-start scenarios, rapid phase-angle adjustments can cause frequency fluctuations due to the coupling between the frequency and phase angle. This coupling often leads to frequency overshoot and decreased system stability. To address this challenge, this paper proposes an enhanced parallel restoration strategy for a multi-source black start. Optimizing phase-angle control reduces the dependency on phase-locked loops (PLLs), mitigates phase-angle difference jumps, and accelerates the pre-synchronization process. Furthermore, a linear active disturbance rejection controller (LADRC) dynamically compensates for frequency fluctuations, effectively decoupling the frequency from the phase angle. This approach improves synchronization accuracy and enhances parallel reliability among multiple distributed energy resources (DERs). Simulation results show that the proposed method suppresses frequency overshoot and system disturbances during a multi-source black start, significantly enhancing microgrid restoration capability and operational stability.